The Chilean experience with national cancer plan and law: a cooperative bridge between the civil society and the government. - Quijano , Esteban; Corbeaux, Tatiana; Villota, Claudio; Goic, Carolina; Jimenez de la Jara, Jorge; Soza-Ried, Cristian (International Journal of Scientific Research and Management (IJSRM), 2022)
In Chile, like in other Latin American countries, cancer incidence is rising rapidly with a massive social and economic burden, and this situation has worsened after the COVID19 outbreak. In 1986 the Chilean government created two antineoplastic drugs for adults (PANDA) and children (PINDA). Later, several cancers, cancer prevention plans and palliative services were covered by the GES/AUGE plan. However, the lack of a national cancer register, disparities in coverage and centralisation of specialists and oncologic infrastructure made the creation of a new National Cancer Plan necessary. Civil society, particularly non-governmental organisations (NGOs), pushed for a National Cancer Law as the legal framework for the National Cancer Plan. Their role is crucial to expose the patient perspective. Likewise, the collaborative work with clinic specialists, scientific societies, government and stakeholders is essential to face a multifactorial disease such as cancer. In this article, we analyse the role of civil society, particularly NGOs, in developing the Chilean National Cancer Plan and the National Cancer law. Through public consultation (including the Massachusetts Institute of Technology-COLAB platform, telephone and online surveys), we show that the community's main concerns were treatment financing, coverage, transparency of public policies, integral cancer care, health promotion and prevention. Historically, NGOs have played an assistant role; however, this is changing towards a more preponderant role in public policies, as seen in other developed countries, giving the strength to the civil society to collaborate in the construction of patient-centred cancer policies.Key words: Cancer policies, Cancer law, NGO, Chile, civil society.